INTRODUCTION—Frontiers in Motion (Frontem): Comparative Perspectives on European Borders, Cross-Border Cooperation, and Integration - Wassenberg, Birte (Borders in Globalization Review, 2023)
This special section, edited by the author, presents five articles developed from the Frontiers in Motion (Frontem) doctoral seminar held in Strasbourg, France, in October 2021, on “Borders in Motion: Borders, Cross-Border Cooperation and European Integration”. The event was organized within the framework of the Jean Monnet Network, “Frontières en mouvement: quels modèles pour l’Union Européenne (Frontem)?” (“Frontiers in Motion: what models for the EU?”), which aimed at fostering knowledge and practice exchanges on cross-border management models and various perceptions of borders across European (and North American) border regions. The diverse contributions illustrate the complexity of borders in Europe and that there has never been an abolition of all types and functions of borders in the European Union (EU). It therefore offers a critical reading of the “Europe without borders” model of the EU (Cooper 1989; Brunet-Jailly & Wassenberg 2020). Note: The network Frontières en mouvement: quels modèles pour l’UE? (611115-EPP-1-2019-1-FR-EPPJMO-NETWORK) is a Jean-Monnet Network supported by the EU’s Erasmus+ program for the period between 2019 and 2023 under the leadership of the author.